Isolation and characterization of the midgut microbiota of Aedes albopictus to identify suitable candidates for paratransgenesis - Darbandsari, Mersa; Asgari, Majid; Okwarah, Patrick (European Journal of Public Health, 2025)
Aedes albopictus is a widely recognized carrier of various pathogens. Its resilient characteristics enable it to easily spread across diverse climates. The microbiota in the midgut of mosquitoes plays a crucial role in the interactions between the host and pathogens and can either enhance or reduce the ability of the insect to transmit diseases. Hence, determining the microorganisms present in the mosquito’s digestive system could be a promising ap proach to developing an effective method of controlling them. Hence, the aim of this study was to investigate the microbial compositions in the midguts of Ae. albopictus mosquitoes collected from the fields of Sistan and Baluchestan Province. The midguts of 60 female mosquitoes were dissected, and their related bacteria were determined using the culture-dependent method. Different colonies were differentiated using the biochemical tests followed by 16S rRNA gene sequencing. The isolated bacteria were identified as belonging to the Asaia, Delftia, Serratia, Aeromonas, Paracoccus, and Planomicrobium genera based on biochemical and molecular ana lysis. The findings obtained in this study were largely consistent with earlier studies conducted on mosquitoes gathered from different regions throughout the world. Overall, the findings could enhance our understanding of the microbial diversity in Ae. albopictus and aid in the identification of a potent and widespread bacterium for the development of a paratransgenesis tool to combat Aedes-borne infectious diseases.
European Journal of Public Health, Vol. 35, Supplement 1, i60–i65 © The Author(s) 2025. Published by Oxford University Press on behalf of the European Public Health Association. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (https://creativecommons.org/licenses/by/4.0/), which permits unrestricted reuse, distribu